The Relationship of Learning Strategy Preference and Personality Type - Gary J. Conti; Rita C. Kolody (Adult Education Research Conference, 1999)
This study investigated the relationship of learning strategy preference to personality type. The findings indicate that while overall personality type is not related to learning strategy preference, three of the four indicators of personality type show a relationship to learning strategy preference.